Role of Tissue Factor in Metastasis: Functions of the Cytoplasmic and Extracellular Domains of the Molecule - Bromberg, Michael E.; Sundaram, Ranjini; Homer, Robert J.; Garen, Alan; Konigsberg, William H. (Thrombosis and Haemostasis, 1999)
Tissue factor (TF) is a transmembrane glycoprotein that complexes with factor VIIa to initiate blood coagulation. It was reported in an earlier study that expression of high levels of TF in a human melanoma cell line promotes metastasis, and that the cytoplasmic domain of TF is required for this metastatic effect. To analyze the functions of the cytoplasmic and extracellular domains of TF in metastasis, two TF mutants were constructed; in one mutant alanine was substituted for each of the three serine residues in the cytoplasmic domain, preventing phosphorylation; in the other mutant alanine was substituted for four key residues in the extracellular domain, preventing binding of factor VIIa and consequently eliminating the initiation of blood coagulation by the TF-VIIa complex. Melanoma lines expressing high levels of either mutant form of TF were weakly metastatic in SCID mice, indicating that phosphorylation of the cytoplasmic domain and formation of a complex with VIIa by the extracellular domain are required for the full metastatic effect of TF. It was also found that increasing TF expression in human melanoma cells does not increase expression of vascular endothelial growth factor or promote growth and vascularization of tumors derived from the melanoma cells, suggesting that TF acts by a mechanism other than angiogenesis to promote metastasis.